Comparison of bioactive components in pressurized and pasteurized longan juices fortified with encapsulated Lactobacillus casei 01 - Pittaya Chaikham (2018)
In this study, longan juice was subjected to a high pressure of 500MPa for 30min and compared with a juice pasteurized at 90°C/2min. Probiotic Lactobacillus casei 01 was fortified into both juices and the shelf life of these products was studied. Their bioactive components such as ascorbic acid, gallic acid and ellagic acid were analyzed by High Performance Liquid Chromatography (HPLC). Total phenolic compounds and 2,2-Diphenyl-1- picrythydrazyl radical-scavenging activity were determined by colorimetric and spectrophotometric methods. It was found that the pressurized longan juice retained higher amounts of bioactive compounds than the pasteurized juice. In terms of storage stability, bioactive compounds in both processed juices decreased according to the increase in storage time. The survivability of probiotic L. casei 01 in both processed juices declined from 9 to 6 log CFU/mL after 4 weeks of storage. © 2012 Taylor & Francis.